Multistatic 3D SAR imaging with coarse elevation and azimuth sampling - Welsh, Richard; Andre, Daniel; Finnis, Mark V. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
It is advantageous to produce Synthetic Aperture Radar (SAR) renderings in three dimensions as these allow the separation of features in height, providing additional target information. A Nyquist sampled 2D SAR aperture produces high quality 3D imagery, however the large scanning time and data storage requirements make this method impractical for use in many scenarios. This paper investigates the formation of 3D target renderings from sparsely sampled 2D aperture Multistatic SAR geometries. The investigation employed both simulations and measured multistatic data collected at the Ground Based SAR (GBSAR) Laboratory at Cranfield University.